2021
DOI: 10.3390/su13094747
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Sustainable Brand Personalities: An Empirical Study

Abstract: Sustainability marketing has emerged as an important trend both in practice and academic literature. The relevant literature has heavily focused on determinations of sustainable consumer behavior, and practitioners have used these results to derive short-term marketing decisions, e.g., adequate pricing of sustainable products. However, no study has scrutinized derivations of sustainable brand personalities or provided important long-term, strategic, managerial implications for marketing managers of sustainable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 74 publications
(110 reference statements)
0
15
0
Order By: Relevance
“…A study by Lee et al (2009) [17] showed that brand personality influences consumers' emotions, and has an effect on consumers' consumption behavior. Furthermore, similar studies indicated several other possible effects of brand personality relevant to marketers: consistency between consumer personality and brand personality, for instance, is linked to an increase in brand attachment [18]; in addition to that, research by Ghantous (2016) [19] showed that brand personality has an impact on the quality of consumer-brand relationships.…”
Section: Brand Personalitymentioning
confidence: 85%
See 2 more Smart Citations
“…A study by Lee et al (2009) [17] showed that brand personality influences consumers' emotions, and has an effect on consumers' consumption behavior. Furthermore, similar studies indicated several other possible effects of brand personality relevant to marketers: consistency between consumer personality and brand personality, for instance, is linked to an increase in brand attachment [18]; in addition to that, research by Ghantous (2016) [19] showed that brand personality has an impact on the quality of consumer-brand relationships.…”
Section: Brand Personalitymentioning
confidence: 85%
“…As pointed out by Lee and Kim (2017) [1], due to minimal product differences in the hospitality industry, brand personality is essential for Airbnb to differentiate from other brands. Symbolic and emotional values are more difficult to copy than product features, and are, therefore, useful to differentiate service brands [19]. Ghantous (2016) [19] also pointed out that brand personality is very important to service brands, such as Airbnb, because it offers the opportunity to position the brands' services as an emotional experience, and thus cater to consumers' emotional needs.…”
Section: Brand Personalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Strong brands [25] can be sources of firms' competitive advantage and positively affect corporate revenue and shareholder equity [26,27]; however, global brands may be adversely affected during a turbulent time [16,26,28,29]. Furthermore, it should be noted that brand equity and brand value change in response to a firm's sustainable management strategy [12,[30][31][32][33][34][35][36].…”
Section: Global Brandingmentioning
confidence: 99%
“…In 2020, the COVID-19 pandemic has caused tremendous threats to global public health and brought about widespread political, economic, and financial collapse [37]. Given the negative effects of environmental uncertainty on business operations, further analyses of the evolution and sustainability of global brands should be expected [32,35,36]. Since different global brands may exhibit different growth trajectories and distinct transformation processes, examining the pattern of changes over time via data science is worthwhile.…”
Section: Global Brandingmentioning
confidence: 99%